2019
DOI: 10.32614/rj-2018-056
|View full text |Cite
|
Sign up to set email alerts
|

Snowboot: Bootstrap Methods for Network Inference

Abstract: Complex networks are used to describe a broad range of disparate social systems and natural phenomena, from power grids to customer segmentation to human brain connectome. Challenges of parametric model specification and validation inspire a search for more data-driven and flexible nonparametric approaches for inference of complex networks. In this paper we discuss methodology and R implementation of two bootstrap procedures on random networks, that is, patchwork bootstrap of Thompson et al. (2016) and Gel et … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Thus, to estimate the parameters in these models, extending the CS method could be an interesting research problem. Secondly, for the parameters in different network models and the properties of the network, the bootstrap estimator of the parameters deserves a separate study; see [35,15,8] for further discussions. Thirdly, we have regarded the network structure and nodal features as fixed during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to estimate the parameters in these models, extending the CS method could be an interesting research problem. Secondly, for the parameters in different network models and the properties of the network, the bootstrap estimator of the parameters deserves a separate study; see [35,15,8] for further discussions. Thirdly, we have regarded the network structure and nodal features as fixed during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies directly perform bootstrapping on the graph structure and not on underlying data (Chen et al 2018;Levin and Levina 2019), a similar idea has been previously suggested (Friedman et al 1999). To the best of our knowledge, it has not yet been applied in climate science.…”
Section: B Distribution-preserving Ensemblesmentioning
confidence: 97%
“…There have been a few attempts to incorporate the bootstrap into the network context because the bootstrap is an important, general purpose statistical tool, but one whose i.i.d. assumptions are violated in most network contexts (Chen et al, 2018;Levin & Levina, 2019;Bhattacharyya & Bickel, 2015;Lunde & Sarkar, 2019;Chen & Onnela, 2019;Green & Shalizi, 2022;Li et al, 2020;Krivitsky et al, 2011;Desmarais & Cranmer, 2012b). Our proposal is closer to the parametric bootstrap of (Schmid & Desmarais 2017), which generates bootstrapped networks using MPLE ERGM parameters of a single observed network to estimate valid confidence intervals of ERGM parameters.…”
Section: Bootstrapmentioning
confidence: 98%